Identifying patients at risk for myasthenic crisis with hemogram and inflammation-related laboratory parameters – a pilot study - Mehnert, Anne; Bershan, Sivan; Kollmus-Heege, Jil; Gerischer, Lea; Herdick, Meret Luise; Hoffmann, Sarah; Lehnerer, Sophie; Scheibe, Franziska; Stascheit, Frauke; Stein, Maike; Buchan, Alastair M.; Meisel, Andreas; et al. (Frontiers in Neurology, 2024)
Background Myasthenia gravis (MG) is a rare autoimmune disease characterized by fatigable weakness of the voluntary muscles and can exacerbate to life-threatening myasthenic crisis (MC), requiring intensive care treatment. Routine laboratory parameters are a cost-effective and widely available method for estimating clinical outcomes of several diseases, but so far such parameters have not been established to detect disease progression in MG. Methods We conducted a retrospective analysis of selected laboratory parameters related to inflammation and hemogram for MG patients with MC matched to MG patients without MC. To identify potential risk factors for MC, we applied time-varying Cox regression for time to MC, and as a sensitivity analysis generalized estimating equations logistic regression for the occurrence of MC at the next patient visit. Results 15 of the 58 examined MG patients suffered at least one MC. There was no notable difference in the occurrence of MC by antibody status or sex. Both regression models showed that higher counts of basophils (per 0.01 units increase: HR = 1.32, 95% CI =1.02-1.70), neutrophils (per 1 unit increase: HR = 1.40, 95% CI = 1.14-1.72), and potentially leukocytes (per 1 unit increase: HR = 1.15, 95% CI = 0.99-1.34), and platelets (per 100 units increase: HR = 1.54, 95% CI = 0.99-2.38) may indicate increased risk for a myasthenic crisis. Conclusion This pilot study provides proof of concept that increased counts of basophils, neutrophils, leukocytes, and platelets may be associated with a higher risk for developing MC in patients with MG.